KEBIJAKAN DIVIDEN, REPUTASI AUDITOR DAN FAKTOR FAKTOR PENENTU NILAI PERUSAHAAN - Trinita, Sella; Djashan, Indra Arifin (E-Jurnal Akuntansi TSM, 2024)
This study aims to obtain empirical evidence regarding the influence of dividend policy, public accounting firm reputation, and other factors on firm value. In this study, there are seven independent variables, namely dividend policy, profitability, capital structure, liquidity, firm size, firm age, and public accounting firm reputation. The sample consists of 105 data points from 35 companies in the consumer cyclicals and consumer non-cyclicals sectors listed on the Indonesia Stock Exchange (IDX) for the 2020–2022 period. The sample selection was conducted using the purposive sampling method, while data analysis was performed using multiple regression analysis. The results indicate that dividend policy, profitability, and capital structure have an impact on firm value.